2012
DOI: 10.1088/1367-2630/14/2/023037
|View full text |Cite
|
Sign up to set email alerts
|

Inter-dot coupling and excitation transfer mechanisms of telecommunication band InAs quantum dots at elevated temperatures

Abstract: We investigate the photoluminescence temperature dependence of individual InAs/InGaAlAs quantum dots emitting in the optical telecommunication bands. The high-density dots are grown on InP substrates and the selection of a smaller dot number is done by the processing of suitable nanometer-sized mesas. Using ensembles of only a few dots inside such mesas, their temperature stability, inter-dot charge transfer, as well as carrier capture and escape mechanisms out of the dots are investigated systematically. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…The nature of the carrier escape mechanism has been discussed with the ratio of [41][42][43][44] v ¼ E a =DE;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the carrier escape mechanism has been discussed with the ratio of [41][42][43][44] v ¼ E a =DE;…”
Section: Discussionmentioning
confidence: 99%
“…In the case of correlated electron-hole (e-h) escape, ¼ 1 = 2 is satisfied. 42 In the case of InAs/InGaAlAs 44 and InAs/InP 41 emitting in the 1.55-lm band, the authors concluded ¼ 1 = 2 , that is, the mechanism behind the thermal escape was suggested to be a correlated e-h pair escape. In our present InGaSb/AlGaSb, QW sample also emitting in the 1.55-lm band, ¼ 0.12 is obtained and thereby the single carrier (hole) escape mechanism dominates.…”
Section: Discussionmentioning
confidence: 99%
“…When ν = ½, the carrier escape is in the form of correlated electron-hole pairs and this mechanism was observed with GaInP/AlGaInP QW, 35) InAs/GaAs QD, 36) InAs/InP QD, 37) and InAs/InGaAlAs QD. 38) This mechanism is probable when the band discontinuities both in the conduction and valence bands have relatively large values for carrier confinements. When ν < ½, single carrier escape mechanism dominates 36) and this is applied in the present GaSb/AlGaSb case.…”
Section: Carrier-escape Mechanism and Comparison Between Qw-imf And Qmentioning
confidence: 99%
“…With the higher excitation, population of the lowest energy states of larger dots are saturated, and the population of their excited states and carrier transfer to smaller QDs with higher QD-state energies take place through coupled excited states. 29 Then, when the conduction-band QD-state energies of dominantly luminescent QDs come to near resonance with the SC-DOS, the SC recombination rate reaches the maximum as shown in Fig. 7.…”
Section: Discussionmentioning
confidence: 95%